Establishing a Zebrafish Cutaneous T-Cell Lymphoma Therapeutic Screening Platform - Tuzi, Lissandra (Université d'Ottawa | University of Ottawa, 2025)
Cutaneous T-cell lymphoma (CTCL) is a rare non-Hodgkin’s lymphoma involving T-cells which home to the skin, with poor prognosis for advanced stages of disease. Due to complex genetics, epigenetics and environmental factors, the current in vitro and in vivo models have been limited in their ability to recapitulate and study the disease. To address this gap, a two-pronged approach to generate zebrafish models of CTCL was undertaken. The larval zebrafish xenograft platform was optimized and employed using humanized GSS zebrafish larvae which express 3 human hematopoietic-specific cytokines (GM- CSF, SCF, SDF1α) to improve cancer cell engraftment. Following dose optimization of a number of agents and drug combinations, only combination vorinostat and gemcitabine showed a response in keeping with clinical responses observed in clinic, despite their typical use as monotherapies. A novel humanized, lymphoid-tailored zebrafish model expressing human IL-2, IL-5, IL-7, IL-15, DLL4, and SDF1α was also being generated to further improve lymphoid tumour engraftment in zebrafish larvae. Pilot studies using recombinant cytokines in vivo show promise using IL-2 and IL-15 for Hut78 cells xenografts, supporting the generation of these humanized zebrafish for future CTCL modelling. In parallel, the first transgenic zebrafish model which expresses human STAT3, a key signaling molecule frequently amplified in CTCL pathogenesis, using the T-cell specific zebrafish lck promoter was generated. Early characterization confirmed successful expression of the transgene by qPCR, and RNA sequencing suggested differential gene expression in the transgenic larvae. Together, these two systems represent the first zebrafish models of CTCL, establishing tools for further development to understand disease pathogenesis and evaluate drug responses in vivo.
Keywords: Zebrafish; Cutaneous T-cell Lymphoma; In vivo Disease Modelling; Therapeutic Screening